GLOBAL DILEMMA OF NUCLEAR PROLIFERATION: THE CASE OF IRAN - FRANCIS OSAYI OSADEBAMWEN (International Studies Journal)
The need for the international community to get her engagement right is crucial for the sustenance of Peace and security. The quest for self-preservation through the acquisition of nuclear weapons is often seen by other states as threat to their own existence. To balance the equation, supposed threatened states, irrespective of the cost implication, whether financially buoyant (as Iran) or not (as North Korea), joined the arms race. This of course has put a strain on global peace and security. The questions that this paper seeks to investigate are: If Iran has the intention of nuclear armament, why did she accede to all known conventions and treaties meant to rid the world of WMDs? Why do the US and the global community fear nuclear Iran? And what implication does nuclear Iran has for global peace and stability particularly in the Middle East region? The study adopts national interest as its theoretical framework. It finds that nuclear Iran poses a grave danger in the Middle East region and therefore recommended that there should be restrain in handling Iran and other middle level nuclear states.